Does the vaccination against tick-borne encephalitis offer good value for money for incidence rates below the WHO threshold for endemicity?: A case study for Germany - Müller, Malina; Lintener, Hannah; Henkel, Vivien; Pilz, Andreas; Halsby, Kate; Malerczyk, Claudius; Madhava, Harish; Moïsi, Jennifer C.; Yu, Holly; Schley, Katharina (Vaccines, 2024)
Tick-borne encephalitis (TBE) is a viral infection affecting the central nervous system (CNS) with potential long-term consequences including neurological sequelae. Vaccination is critical to reduce TBE morbidity and mortality, as no antiviral treatment is available. The World Health Organization (WHO) defines areas with an incidence of ≥5 cases/100,000 PPY as highly endemic and recommends that vaccination is offered to all individuals in these areas. However, access to TBE vaccination depends on recommendations and funding by national or subnational decision-makers. We assessed if TBE vaccination could offer good value for money at incidences below this threshold. Methods: A closed-cohort Markov model was developed to estimate the cost-effectiveness of TBE vaccination. We compared primary vaccination applied to the whole population (aged above 1 year) and to a subpopulation aged between 60 and 85 years to a scenario without vaccination. Since TBE incidence is often underestimated, we included under-ascertained TBE cases and non-CNS TBE infections. Germany was used as a case study due to the availability of detailed incidence data. Results: Our incidence threshold analysis showed that TBE vaccination offers good value for money well below the WHO threshold in most of the analyzed scenarios. Conclusions: Our results support a recommendation for TBE vaccination even in settings with low numbers of reported cases, especially for older patients. Furthermore, this analysis identified major research gaps regarding the costs, utilities, and clinical progression of TBE.
Gesehen am 04.04.2025